The 5 conversations that really matter in business: transforming trust, engagement and performance at work. Issue 4 (1st June 2015) - Purse, Nigel
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to outline five conversations that leaders must hold to build trusting relationships. People's engagement at work correlates directly with the quality of relationship they have with their line manager. Leaders need to be supported to develop their capabilities in holding conversations, but more importantly to recognize the power of authenticity. Design/methodology/approach – This paper is based on the author's work with managers and leaders in organizations around the world. Findings – Holding authentic conversations that focus on the five areas identified will build trust which, in turn, will improve engagement and ultimately drive performance. Originality/value – Leaders are often expected to focus on visionary, decisive and driving action. This paper proposes that this is not enough; building trusting relationships must lie at the heart of effective leadership. It identifies five critical conversations that line managers as leaders must have to build trusting relationships.